Clearing gang- and drug-involved nonfatal shootings. Issue 4 (10th March 2021) - Barao, Lisa; Braga, Anthony A.; Turchan, Brandon; Cook, Philip J.
Abstract : Purpose: Clearance rates for nonfatal shootings, especially cases involving gang- and drug-related violence, are disturbingly low in many US cities. Using data from a previously completed project in Boston, we explore the prospects for improving gang/drug nonfatal shooting cases by investing the same investigative effort found in similar gang/drug gun murder cases. Design/methodology/approach: Our analyses primarily focus on a sample of 231 nonfatal shootings that occurred in Boston from 2010 to 2014. Logistic regressions are first used to analyze differences in the likelihood of case clearance for gang/drug nonfatal shooting cases relative to other nonfatal shooting cases. Independent samples t -tests are then used to compare the investigative characteristics of these two different kinds of nonfatal shootings. Next, independent samples t -tests are used to compare the investigation of gang/drug gun assaults relative to the investigation of very similar gang/drug gun homicides. Findings: Results demonstrate that the odds of clearing gang/drug nonfatal shootings are 77.2% less likely relative to the odds of clearing nonfatal shootings resulting from other circumstances. This stark difference in clearance rates is not driven by diminished investigative effort, but investigative effort does matter. Relative to gang/drug gun assaults, gang/drug gun homicides have much higher clearance rates that are the result of greater investigative resources and effort that produces significantly more witnesses and evidence, and generate more forensic tests and follow-up investigative actions. Originality/value: Gang- and drug-related violence generates a bulk of urban nonfatal shootings. Low clearance rates for nonfatal shootings undermine police efforts to hold offenders accountable, disrupt cycles of gun violence, and provide justice to victims. Police should make investments to improve investigative effort such as handling these cases with the same vigor as homicide cases.